Unlocking the mysteries behind baby viral videos. - Chung, You Lun. (2012)
With the rise of social media platforms, sharing online content has integrated into our everyday lives. Online content that contains viral elements will effortlessly spread through the Internet as users share among their peers. Mysteriously, videos containing baby content are shared widely and received millions of views. Although there are a few researches that explored how videos become viral, minimal research has been done to understand the complexity behind baby-related viral videos. As a result, this research will investigate the uncanny Internet phenomenon – Baby-related Viral Videos.